Relationship of inhibition of prostaglandin biosynthesis by analgesics to asthma attacks in aspirin-sensitive patients. - Szczeklik, A (1975)
Eleven patients with asthma and aspirin hypersensitivity have been challenged with eight non-steroidal anti-inflammatory drugs. Each drug was given by mouth in at least three different doses and the patients' symptoms and peak expiratory flow (PEF) rates were observed over a three-hour period. Indomethacin 5 mg caused bronchoconstriction in all patients. Therapeutic doses of mefenamic or flufenamic acid caused bronchoconstriction in most patients. Phenylbutazone 200-400 mg induced a moderate fall in PEF. There were no reactions to therapeutic doses of salicylamide, paracetamol, benzydamine, and chloroquine. Microsomal prostaglandin synthetase, activity was inhibited by aspirin, indomethacin, mefenamic acid, flufenamic acid, and phenylbutazone. The other four drugs had no inhibitory effect. We suggest that precipitation of attacks in asthmatic patients hypersensitive to certain anti-inflammatory drugs is related to drug's ability to inhibit prostaglandin biosynthesis.